CPNA-method for ES detection using hydrogen ion accelerators operating in batch-pulse mode - Gavrish, Yu.N.; Sidorov, A.V; Fialkovsky, A.M. (Вопросы атомной науки и техники, 2004)
A new nuclear method CPNA (complex pulsed neutron analysis) for detection of explosive substance (ES) is
suggested. The essence of the method is the following. Information on ES presence can be obtained from analysis of
energy spectra of γ-quanta produced as a result of nuclear reactions of neutron pulse radiation interaction with nuclei
of characteristic elements constituents of ES. Based on optimizing calculations of neutron radiation parameters to
provide most effective detection of ES, a batch-pulse operating mode of the hydrogen ion accelerator has been suggested. Запропоновано новий ядерно-фізичний метод виявлення вибухових речовин (ВР). Інформація про наявність ВР може
бути отримана з аналізу енергетичних спектрів гамма-випромінювання, отриманих у результаті ядерних реакцій
взаємодії імпульсного періодичного нейтронного випромінювання з ядрами характерних елементів, що входять до складу ВР. На підставі розрахунків оптимізації параметрів нейтронного випромінювання для ефективного виявлення
вибухових речовин запропоновано використовувати пакетно-імпульсний режим роботи прискорювача іонів водню. Предложен новый ядерно-физический метод обнаружения взрывчатых веществ (ВВ). Информация о наличии ВВ может быть получена из анализа энергетических спектров гамма-излучения, образуемых в результате ядерных реакций
взаимодействия импульсного периодического нейтронного излучения с ядрами характерных элементов, входящих в состав ВВ. На основании расчетов оптимизации параметров нейтронного излучения для эффективного обнаружения
взрывчатых веществ предложено использовать пакетно-импульсный режим работы ускорителя ионов водорода.